Understanding student early departure from a Master of Public Health programme in South Africa - T Dlungwane; A Voce; R Searle; J Wassermann (South African Medical Association, 2017)
Background. Student departure from university without completing a qualification is a major concern in higher education. Higher Education South Africa reported that in undergraduate studies, 35% of students depart after the first year and only 15% of students who enrol complete their degree within the minimum permissible time. At postgraduate level, the departure from Masters programmes in South Africa (SA) ranged from 30% to 67% in 2010. Early departure refers to students who leave an academic programme within the first semester of commencing their studies. At one SA university, there were a total of 109 first-time Master of Public Health (MPH) student registrations in 2013 and 2014. By the end of the first semester in the respective years, a total of 27 students actively deregistered from the programme and 11 students did not sit the first-semester examinations, representing an aggregate 35% rate of early departure. The factors associated with early departure at the University of KwaZulu-Natal are not well understood.Objective. To understand factors associated with early departure in the MPH programme at the University of KwaZulu-Natal.Method. A mixed-methods design was implemented. Students who departed within the first semester of commencing the MPH programme in 2013/2014 were followed up. Data were collected using self-administered questionnaires and in-depth interviews.Results. Failure to balance work and academic obligations with poor time management, stress and academic demands related to the programme, and insufficient academic progress were found to be associated with student early departure from the MPH programme.Conclusion. Student early departure from the MPH programme was influenced by multifaceted factors. Senior students can mentor new students as early as possible in their programme. The orientation block should include development activities such as time management, stress management and effective study skills to assist mature students to cope with the demands of part-time postgraduate studies.